QUALITY MANAGEMENT OF TECHNICAL MAINTENANCE OF TRUCKS - Zhumatayeva G.; Bitileuova Z.; Baiburaeva Zh.; Zhanbirov Zh. (Academic Journal of Physical and Chemical Sciences, 2020)
The problem of providing vehicles with high-quality and timely maintenance and repair reaches a critical level and is a barrier for the development of the car market in the republic. In this context, management of technical operation of trucks is complicated, which requires the improvement of maintenance system and repairs necessary to reduce the cost of maintenance. To improve the competitiveness of trucks, it is necessary to ensure a high level of quality at the stages of development and production, and maintain the achieved level of quality during operation. One of the most promising ways to improve the operational reliability of trucks is quality management during maintenance and repairs. An analysis of recent studies and publications devoted to this issue showed that studies of the technical condition of cars are associated with road safety, cost-effectiveness and comfort, and largely depend on operating conditions. The available significant information base allows us to develop new process technologies to improve the operational reliability of cars.